Contextual reliability discounting in welding process diagnostic based on DSmT. Issue 2 (23rd May 2014) - Jamrozik, Wojciech
Abstract The monitoring and diagnosing of the welding process is an important task in assuring the quality of welded joints. Observation of such a dynamic process is often performed by measuring various signals of different modality. The main problem is how to use several of the possible signals simultaneously. Many techniques that can deal with this kind of task were elaborated and introduced in practical application. One of these is decision fusion, with a group of methods based on belief function theories: Dempster–Shafer and Dezert–Smarandache (DSmT). In this paper, extended fusion scheme for assessment of welding process condition, with contextual discounting of evidence sources reliability in DSmT framework, is presented. Discounting operation was used to distinguish the objective ability of each evidence source, to give a correct assessment of process condition. To validate this method, several series of welded joints representing different process conditions that result in various joint quality were made. On the basis of performed research, it was proven that contextual reliability discounting leads to increase of the condition recognition accuracy.